2022
DOI: 10.3390/vaccines10122156
|View full text |Cite
|
Sign up to set email alerts
|

A Vaccine Targeting Ovine Herpesvirus 2 Glycoprotein B Protects against Sheep-Associated Malignant Catarrhal Fever

Abstract: Malignant catarrhal fever (MCF) is a complex and often fatal disease of ungulates. Effective vaccines are needed to avoid MCF outbreaks and mitigate losses. This study aimed to evaluate a sheep-associated MCF (SA-MCF) vaccine candidate targeting ovine herpesvirus 2 (OvHV-2) glycoprotein B (gB). Rabbits were used as a laboratory animal model to test the safety, immunogenicity, and protective efficacy of a chimeric virus consisting of a recombinant, non-pathogenic strain of alcelaphine herpesvirus-1 encoding OvH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Therefore, it is possible that two animals showing 100% inhibition in plasma diluted at 1:32 indeed have highly different titers of neutralizing antibodies. Overall, antibody responses obtained in this study are in accordance with previous SA-MCF vaccine trials using BoHV-4 or AlHV-1-vectored OvHV-2 gB vaccine candidates tested in the rabbit model, where the presence of anti-OvHV-2-gB antibodies and protection were also not correlated [ 24 , 31 ]. Taken together, these results suggest that other immune factors, including cellular immunity, are critical for protection against SA-MCF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, it is possible that two animals showing 100% inhibition in plasma diluted at 1:32 indeed have highly different titers of neutralizing antibodies. Overall, antibody responses obtained in this study are in accordance with previous SA-MCF vaccine trials using BoHV-4 or AlHV-1-vectored OvHV-2 gB vaccine candidates tested in the rabbit model, where the presence of anti-OvHV-2-gB antibodies and protection were also not correlated [ 24 , 31 ]. Taken together, these results suggest that other immune factors, including cellular immunity, are critical for protection against SA-MCF.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the absence of OvHV-2 DNA in the blood and tissues of the two animals that did not develop SA-MCF upon challenge suggests that protection was achieved by preventing OvHV-2 infection rather than by a reduction in viral load. This, along with other studies targeting OvHV-2 gB as a vaccine [ 24 , 31 ], confirms that sterile immunity based on OvHV-2 gB can be achieved by vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…The use of the AlHV-1 strain deleted for ORF73 is of great interest because the strain is unable to establish a latent infection and is therefore rapidly controlled and cleared. A recent study demonstrated that the AlHV-1 strain deleted for ORF73, where the coding sequence of gB (ORF8) was replaced by OvHV-2 gB, was able to replicate in vitro and provide protection against an intranasal challenge with OvHV-2 [ 159 , 160 ]. Thus, the recombinant ORF73-deleted AlHV-1 strain represents a very promising tool for future vaccine development in the near future.…”
Section: Current Status Of Diagnosis and Vaccinesmentioning
confidence: 99%